Respuesta :
Answer:
x=-9/10
Step-by-step explanation:
2x+8x+16=7
Step 1: Simplify both sides of the equation.
2x+8x+16=7
(2x+8x)+(16)=7(Combine Like Terms)
10x+16=7
10x+16=7
Step 2: Subtract 16 from both sides.
10x+16−16=7−16
10x=−9
Step 3: Divide both sides by 10.
10x/10
=
−9/10
x=-9/10
Answer:
x = - 4 ± [tex]\sqrt{7}[/tex]
Step-by-step explanation:
Given
x² + 8x + 16 = 7 ( subtract 16 from both sides )
x² + 8x = - 9
Using the method of completing the square
add ( half the coefficient of the x- term)² to both sides
x² + 2(4)x + 16 = - 9 + 16
(x + 4)² = 7 ( take the square root of both sides )
x + 4 = ± [tex]\sqrt{7}[/tex] ( subtract 4 from both sides )
x = - 4 ± [tex]\sqrt{7}[/tex]
Then
solutions are x = - 4 - [tex]\sqrt{7}[/tex] , x = - 4 + [tex]\sqrt{7}[/tex]